A New ZVS Nonisolated Bidirectional DC-DC Converter with Minimal Auxiliary Element - Nasrin Asadi Madiseh; Majid Delshad (Journal of Intelligent Procedures in Electrical Technology, 2013)
In this paper, a new nonisolated bidirectional buck–boost dc–dc converter is introduced. The proposed converter can be operated under ZVS condition and fixed switching frequency regardless of the direction of power flow. To provide ZVS condition for switches a simple auxiliary circuit is used, that consists of an auxiliary inductor and a coupled winding to main inductor. Due to ZVS operation of switches, the reverse recovery problem of the body diode of the switches does not occur. Moreover, to provide soft switching any extra switch is not used in this converter, so its implementation and control is very simple. The experimental and simulation results of the proposed bidirectional converter are given to confirm the theoretical analysis.